Analisis Pengaruh Physical Evidence, Price, Service, Location Dan Salesperson Terhadap Buying Intention Di Spazio Office Building - Hartanto, Cynthia Christina (Jurnal Strategi Pemasaran, 2014)
Developments property bussiness in Surabaya has grown rapidly both price and volume of sales that cause property business competition is getting tight. Knowing what are the preferences of consumers buying intention is essential for companies to be able to sharpen their competitiveness in order to increase product sales. In this case, the researcher intends to use the title "Analysis the influence of Physical evidence, Price, Service, Location, Salesperson to Buying intetion at Spazio Office Building".This is a quantitative research with 100 respondent. The technique of data collection is done by a non-probability sampling, purposive sampling technique. Method of data processing is done by using the validity, reliability, descriptive statistics analysis, and classical assumption. While the data analysis method used is by using multiple linear regression analysis, the F test and t test. The survey results revealed that the variable Physical Evidence, Price, Service and salesperson each have a significant influence on the buying intention partially at Spazio office building. While the variable location is not a significant impact on the buying intention at Spazio Office Building.